The XXXVII OSA'90 Report - SANKIEWICZ, Marianna (Archives of Acoustics, 1991)
The annual conferences of Polish acousticians sponsored by the Committee on Acoustics of the Polish Academy of Sciences and by the Polish Acoustical Society, have been organized for the thirty seven years, under a traditional name of the Open Seminar on Acoustics (OSA), actually by the seven regional branches of the Society, subsequently. This year the site of the OSA'90 was Gdańsk, and particularly its largest academic institution, widely known over the world of over eighty years, namely the Technical University of Gdańsk.